Pszczoły i ich produkty na usługach zdrowia ludzi - Mruk, Henryk (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
Bees are associated with the entire ecosystem by pollinating flowers. Their work translates into obtained crops from trees and plants. They also provide many products that people use in everyday life. Honey provides people with simple sugars, vitamins, and mineral salts. Bee venom is used to treat rheumatic diseases. Propolis is used for inflammation and minor wounds and mycoses. Royal jelly provides life-giving vitamin E. Meads allow you to build social relationships. Wax figurines enrich the sphere of artistic sensations. Observation of the bee community can be an inspiration to build partnership and relationships in interpersonal communication
Keywords: health; bee products; honey